2022
DOI: 10.1128/iai.00682-21
|View full text |Cite
|
Sign up to set email alerts
|

Human Intelectin-1 Promotes Cellular Attachment and Neutrophil Killing of Streptococcus pneumoniae in a Serotype-Dependent Manner

Abstract: Human intelectin-1 (hIntL-1) is a secreted glycoprotein capable of binding exocyclic 1,2-diols within surface glycans of human pathogens such as Streptococcus pneumoniae , Vibrio cholerae , and Helicobacter pylori . For the latter, lectin binding was shown to cause bacterial agglutination and increased phagocytosis, suggesting a role for hIntL-1 in pathogen surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Previously, we found that hItln1 exhibits serotype-specific binding to isolates of Streptococcus pneumoniae ( 14 ). Others have noted binding to different bacterial species considered pathogenic, suggesting that hItln1 targets pathogens ( 17 , 18 ). Because hITLN1 is expressed in the small intestine ( 19 ), we assessed the binding of recombinant hItln1 to a collection of human gut microbial strains by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that hItln1 exhibits serotype-specific binding to isolates of Streptococcus pneumoniae ( 14 ). Others have noted binding to different bacterial species considered pathogenic, suggesting that hItln1 targets pathogens ( 17 , 18 ). Because hITLN1 is expressed in the small intestine ( 19 ), we assessed the binding of recombinant hItln1 to a collection of human gut microbial strains by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found hItln1 exhibits serotype-specific binding to isolates of Streptococcus pneumoniae ( 14 ). Others have noted binding to different bacterial species considered pathogenic, suggesting hItln1 targets pathogens ( 17, 18 ). Since hItln1 is expressed in the small intestine ( 19 ), we assessed the binding of recombinant hItln1 to a collection of human gut microbial strains by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…The implications of hItln1 binding to these gut-resident species are unclear. The interaction of hItln1 with select pathogens activates macrophage- and neutrophil-mediated killing ( 17, 18, 42 ); however, hItln1-mediated neutrophil activation requires serum components suggesting the bactericidal functions of hItln1 may be limited to the blood. Unlike some intestinal lectins ( 11 ), hItln1 has no known microbial toxicity and, unlike MBL, lacks canonical domains for complement recruitment ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In aneurysm pathogenesis, inflammatory cells migrate to the aneurysmal lesion, perpetuating the inflammatory response and destructive remodeling, including matrix degradation and internal elastic lamina disruption [ 31 ]. The DEG ITLN1 is associated with the innate immune system and defensins, which are predominantly found in neutrophils [ 37 ]. ITLN1 has been reported to be differentially expressed in aneurysm tissue compared to control superficial temporal artery tissue, indicating it may be related to IA-lesion specific signaling at the IA site [ 38 ].…”
Section: Discussionmentioning
confidence: 99%